ESX-1-induced apoptosis during mycobacterial infection: to be or not to be, that is the question - Aguilo, Juan I.; Marinova, Dessislava; Martin, Carlos; Pardo, Julian (Frontiers in Cellular and Infection Microbiology, 2013)
The major Mycobacterium tuberculosis virulence factor ESAT-6 exported by the ESX-1 secretion system has been described as a pro-apoptotic factor by several independent groups in recent years, sustaining a role for apoptosis in M. tuberculosis pathogenesis. This role has been supported by independent studies in which apoptosis has been shown as a hallmark feature in human and mouse lungs infected with virulent strains. Nevertheless, the role of apoptosis during mycobacterial infection is subject to an intense debate. Several works maintain that apoptosis is more evident with attenuated strains, whereas virulent mycobacteria tend to inhibit this process, suggesting that apoptosis induction may be a host mechanism to control infection. In this review, we summarize the evidences that support the involvement of ESX-1-induced apoptosis in virulence, intending to provide a rational treatise for the role of programmed cell death during M. tuberculosis infection.